2020
DOI: 10.1007/s00213-020-05530-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of repeated treatment with monoamine-transporter-inhibitor antidepressants on pain-related depression of intracranial self-stimulation in rats

Abstract: Synaptic neurotransmission with dopamine (DA), norepinephrine (NE), and serotonin (5-HT) is terminated primarily by reuptake into the presynaptic terminal via the DA, NE, and 5-HT transporters (DAT/NET/SERT, respectively). Monoamine transporter inhibitors constitute one class of drugs used to treat pain, and emergence of analgesic effects by these compounds often requires repeated treatment for days or weeks. The present study compared antinociceptive effects produced by repeated treatment with monoamine trans… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 71 publications
1
6
0
Order By: Relevance
“…Second, inflammation and neuropathy in rodents have also been reported to promote dynorphin signaling and KOR activation in the mesolimbic dopamine system, and this enhanced KOR signaling has been implicated in some signs of pain-related behavioral depression (Liu et al, 2019;Meade et al, 2020). We have not found evidence for this type of pain-related activation of KOR signaling in previous studies using both acute and chronic pain manipulations (Leitl et al, 2014a;Leitl et al, 2014b;Negus et al, 2015;Bagdas et al, 2016;Legakis et al, 2020), and the present study is consistent with our own previous findings. Thus, CFA and paclitaxel treatment produced only transient and/or weak evidence for depression of operant responding, so there was little evidence to suggest a KORmediated depressant effect in this study.…”
Section: Discussionsupporting
confidence: 92%
“…Second, inflammation and neuropathy in rodents have also been reported to promote dynorphin signaling and KOR activation in the mesolimbic dopamine system, and this enhanced KOR signaling has been implicated in some signs of pain-related behavioral depression (Liu et al, 2019;Meade et al, 2020). We have not found evidence for this type of pain-related activation of KOR signaling in previous studies using both acute and chronic pain manipulations (Leitl et al, 2014a;Leitl et al, 2014b;Negus et al, 2015;Bagdas et al, 2016;Legakis et al, 2020), and the present study is consistent with our own previous findings. Thus, CFA and paclitaxel treatment produced only transient and/or weak evidence for depression of operant responding, so there was little evidence to suggest a KORmediated depressant effect in this study.…”
Section: Discussionsupporting
confidence: 92%
“…To address these limitations, in Experiment 2, we modified the experimental design and increased the number of pairings between pain exposure and opioid self-administration. We used lactic acid as a noxious stimulus because it can be administered repeatedly without developing tolerance to its pain-related decrease on operant responding (Legakis et al 2020; Miller et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in Experiment 2, we used a different acute pain-related manipulation, daily i.p. injections of lactic acid, which does not require anesthesia (Negus 2013; Pereira Do Carmo et al 2009) and for which tolerance does not develop after repeated exposure (Legakis et al 2020; Miller et al 2015). Furthermore, because the context manipulation in Experiment 1 was ineffective, we simplified the experimental design and eliminated the context in which a noxious stimulus was absent.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, DA is converted into noradrenaline (NA) by DA hydroxylase. Numerous studies (72)(73)(74)(75)(76)(77)(78)(79)(80)(81)(82)(83) confirmed that the dysfunction of monoamine neurotransmitters such as NE, DA, and 5-HT plays a crucial part in the pathogenesis of depressive disorder. Elevated DA, L-DOPA, and vanillylmandelic acid (VMA) levels were found in the hippocampus of CSDSinduced model mice (84,85).…”
Section: Authormentioning
confidence: 95%